Principles of Sincerity and Honest Management in Vocational Secondary Schools from a Hadith Perspective Management - Holid, Agus; Salafiyah, Yuyun; Farisi, Ahmad Nu’man; Mu’in, Abdul; Fauzi, Anis (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the significance of integrity and honest leadership in schools, guided by a hadith from Abu Hurairah (R.A) emphasizing the importance of intentions and truthful behavior. Effective school leadership requires collaboration among principals, staff, students, and parents, fostering a supportive management structure. Consistently applying honesty and integrity can strengthen the organizational culture and bring positive changes. The research employs a literature study method with a descriptive approach to assess the impact of these principles on school performance and stakeholder satisfaction. Continuous education and training for all stakeholders are crucial to enhance understanding and implementation of fair and honest governance. In the long term, these practices promote a positive and transparent school environment.